Gamifying Sustainability: Incorporating a gamification approach for more responsible decision-making - Martínez, Germán; Rocabado, Isabel; Cong Le, Trong; Ansari Vaghef, Alireza; Alabarca, Keila (Acta Herediana, 2026)
In response to the growing need for more responsible decision-making in the tourism sector by consumers and the persistent "attitude-behavior gap," this article presents the development of an innovative project designed to include gamification as part of the online flight booking experience with a sustainability approach. Through the application of a structured gamification approach, based on psychological motivators, the solution integrates mechanics and components to motivate users to make responsible decisions, transforming a transactional process into an engaging and meaningful experience.